The subject composition of relations on social protection of the rights of critical infrastructure workers in Ukraine - Lubinets, D.V. (Аналітично-порівняльне правознавство, 2024)
The article focuses on elucidating the subject composition of relations concerning the social protection rights of critical infrastructure workers in Ukraine. It supports the view that the relations for the social protection of these workers constitute legal relations involving social law subjects. These relations are directed towards establishing the right to social protection of critical infrastructure workers, the realization and enforcement of this right, as well as its protection and restoration in the event of violation. The composition of subjects within the legal relations of social protection for critical infrastructure workers aligns with the array of subjects encompassed by the legal mechanism safeguarding the rights of these workers in Ukraine. This study suggests that the structure of the subjects involved in the social protection of critical infrastructure workers should be conceptualized as a system comprising four distinct groups. The primary group consists of the critical infrastructure workers themselves, who possess and exercise their right to social protection and defend this right through jurisdictional or extra-jurisdictional means. Secondly, a pivotal participant in the social protection relations for critical infrastructure workers is the employer, namely the respective critical infrastructure entity. Employers should perceive workers not merely as industrial resources but as individuals endowed with inherent human dignity, alongside rights and interests that can be safeguarded through social protection measures implemented by employers in Ukraine. Thirdly, public administration entities, along with other public service bodies and their officials, also play a role in the social protection relations for critical infrastructure workers. These bodies and officials, vested with relevant authority, are responsible for executing social protection measures for the rights of critical infrastructure workers and for upholding these workers’ rights. Fourthly, under the current democratization of the social protection system, relationships concerning the social protection of critical infrastructure workers should also encompass civil society entities, notably trade unions, other professional associations of critical infrastructure workers, and human rights non-governmental organizations (specializing in the protection of workers’ rights, including those of young workers). The conclusion of this article synthesizes the findings of the study.